The K153R polymorphism in the myostatin gene and muscle power phenotypes in young, non-athletic men. - Catalina Santiago (Public Library of Science (PLoS), 2011)
The Lys(K)153Arg(R) polymorphism in exon 2 (rs1805086, 2379 A>G replacement) of the myostatin (MSTN) gene is a candidate to influence skeletal muscle phenotypes. We examined the association between the MSTN K153R polymorphism and 'explosive' leg power, assessed during sprint (30 m) and stationary jumping tests [squat (SJ) and counter-movement jumps (CMJ)] in non-athletic young adults (University students) [n = 281 (214 men); age: 21-32 years]. We also genotyped the MSTN exonic variants E164K (rs35781413), I225T, and P198A, yet no subject carried any of these variant MSTN alleles. As for the K153R polymorphism, we found only one woman with the KR genotype; thus, we presented the results only for men. The results of a one-way ANCOVA (with age, weight and height entered as covariates) showed that men with the KR genotype (n = 15) had a worse performance in vertical jumps compared with those with the KK genotype [SJ: vertical displacement of center of gravity (CG) of 35.17 ± 1.42 vs. 39.06 ± 0.39 cm, respectively, P = 0.009; CMJ: vertical displacement of CG of 36.44 ± 1.50 vs. 40.63 ± 0.41 cm, respectively, P = 0.008]. The results persisted after adjusting for multiple comparisons according to Bonferroni. Performance in 30 m sprint tests did however not differ by K153R genotypes. In summary, the MSTN K153R polymorphism is associated with the ability to produce 'peak' power during muscle contractions, as assessed with vertical jump tests, in young non-athletic men. Although more research is still needed, this genetic variation is among the numerous candidates to explain, alone or in combination with other polymorphisms, individual variations in muscle phenotypes.